Equipment diagnostic audit for energy management of central air conditioning systems - Tay, Seow Ngie (2008)
This project aims at developing an equipment diagnostic audit (EDA) model to identify such deficiency with the objective of optimizing overall system efficiency. The EDA model was built based on actual data obtained from a real CACS, the North Spine central air conditioning plant of NTU with an installed cooling capacity of 3500 RT serving a total air conditioning floor area of 50,700 m2. The EDA model has proven to be an effective tool in diagnosing the key factors contributing to inefficiency in chiller plant. Through the application of the EDA procedure, the inefficient operational practices were eliminated and the efficiency of the North Spine CACS had improved drastically since May 2001. This is reflected in the drop in weekly electricity consumption of the plant from 190,000 kWh per week in May 2001 to 110,000 kWh per week in May 2004.